Gambaran Pemberian Vitamin A di Bulan Februari 2023 pada Balita Usia 6-59 Bulan di Wilayah Kerja Puskesmas Jagir Surabaya - Adiiba Dzakiyah Choirunnisa; Aviana Gita Lara; Akas Yekti Pulih Asih (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2023)
Child health problems in Indonesia are currently one of the main problems in the health sector that often occur. Immunization is one way to increase individual immunity against diseases, especially in toddlers. Giving vitamin A to toddlers is very important because it prevents vitamin A deficiency which can cause reduced vision at dusk (night blindness), drying of the epithelial tissue in the eyes and lungs, damage to the eye tissue which causes blindness. This research is a descriptive observational study. February 2023. Toddler posyandu located in the working area of ​​the Jagir Health Center, namely Jagir Village, Darmo Village, and Sawunggaling Village. The data collection technique used secondary data obtained from the results of the recap in February 2023 at the Surabaya City Health Office Platform on Dear Residents Posyandu Toddlers. There are 66 toddlers aged 6-11 months who have not received vitamin A, and there are 242 toddlers aged 12-59 who have also not received vitamin A. From all examinations at each Posyandu toddlers there are still toddlers who have not been given vitamin A In this data it is also possible that there are toddlers who have not been registered in the system so that they are not detected in the examination. Then there are also toddlers who move posyandu but have not been reported. For infants and toddlers who have not received vitamin A, they can visit the Jagir Health Center for vitamin A administration.